2005
DOI: 10.1016/j.biopsycho.2004.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholism is a disinhibitory disorder: neurophysiological evidence from a Go/No-Go task

Abstract: Response inhibition is considered a core dimension in alcoholism and its co-existing disorders. The major objective of this study is to compare the magnitude and spatial distribution of ERP components during response activation and inhibition in alcoholics (N = 30) and normal controls (N = 30) using a visual Go/No-Go task. The results indicate that alcoholics manifest a decreased P3(00) amplitude during Go as well as No-Go conditions. The difference between Go and No-Go processing was more evident in controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
209
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 201 publications
(229 citation statements)
references
References 112 publications
(117 reference statements)
16
209
1
3
Order By: Relevance
“…Using go-nogo tasks several studies from our laboratory have shown P300, delta and theta power differences in alcoholics and high risk individuals (Kamarajan et al, 2004;Kamarajan et al, 2005a;Kamarajan et al, 2005b). In these studies the 'go' trials closely resemble the 'target' trial used in the present study.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Using go-nogo tasks several studies from our laboratory have shown P300, delta and theta power differences in alcoholics and high risk individuals (Kamarajan et al, 2004;Kamarajan et al, 2005a;Kamarajan et al, 2005b). In these studies the 'go' trials closely resemble the 'target' trial used in the present study.…”
Section: Discussionsupporting
confidence: 56%
“…In the Go condition, strong delta band total ERO deficits for alcoholics were observed over frontal, parietal and occipital locations; however, no theta band differences were noted in alcoholics when compared to the controls (Kamarajan et al, 2004). In the high-risk adult population the results for the same task revealed parietal delta and theta band total power reductions for the Go condition (Kamarajan et al, 2005a). The No-go condition also revealed strong delta and theta band ERO differences.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The GNG and SST discriminate between addicted individuals and controls, suggesting that these tasks may operationalize key addiction-related inhibitory deficits (Kamarajan et al, 2005;Lawrence et al, 2009). However, inhibitory performance is also sensitive to situational factors.…”
mentioning
confidence: 99%
“…Further, decreased NoGo-P3 amplitude has also been reported in alcoholics (Cohen et al 1997a;Kamarajan et al, 2005b) as well as in children of alcoholics (Cohen et al 1997b;Kamarajan et al, 2005a). There is a good deal of evidence that P3 responses are primarily the outcome of oscillatory changes in delta and theta rhythms during stimulus processing (Stampfer and Basar 1985;Basar-Eroglu et al 1991, 2001Roschke and Fell 1997;Devrim et al 1999;Demiralp et al 2001).…”
Section: Introductionmentioning
confidence: 94%